Funcionarios. (UNED, 2024)
De izquierda a derecha de pie Elí Marín Hernández, Mario Sibaja Bustamante, Gerardo Munguía Romero, Dionisio Rodríguez Montero, Hubert Gómez Sanabria, Juan Elías Monge Monge, Gerarado Murillo, José Marchena Espinoza, Sandra Guzmán Vindas, Vitalina Hernández Ortega